The Influence of Social Media Engagement and Online Reviews on the Decision to Visit Bandung's Natural Tourist Destination - Farida Akbarina (West Science Social and Humanities Studies, 2026)
The rapid development of digital platforms has significantly transformed tourists’ decision-making processes, particularly in the context of natural tourism destinations. This study aims to analyze the influence of social media engagement and online reviews on tourists’ decisions to visit natural tourism destinations in Bandung, Indonesia. A quantitative research approach was employed by distributing structured questionnaires to 150 respondents who actively use social media and access online tourism reviews. The measurement items were assessed using a five-point Likert scale, and data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25. The results of multiple linear regression analysis indicate that social media engagement has a positive and significant effect on tourists’ visit decisions. Similarly, online reviews were found to have a significant positive influence on the decision to visit. Furthermore, the simultaneous test results demonstrate that both variables jointly contribute significantly to explaining tourists’ visit decisions, accounting for 52.7% of the variance. These findings highlight the crucial role of digital interaction and electronic word-of-mouth in shaping tourists’ behavior. The study provides practical implications for tourism managers and policymakers in Bandung, emphasizing the importance of integrating engaging social media strategies with effective online review management to enhance the attractiveness and competitiveness of natural tourism destinations.